Déficits gemelos en Colombia y Latinoamérica (2018)
Since the recent international financial crisis of 2007-2009 there has been a global debate about twin deficits. The increase in public expenditure to manage the international crisis has generated uncertainty about the sustainability of fiscal and current account deficits. In Europe, Asia, and the United States there exist numerous studies about the topic. In the case of Latin America and Colombia the studies are scarce. This document shows evidence that in Colombia, and in other Latin American countries, current account and fiscal deficits are related. However, in most cases, causality is reverse.